2018
DOI: 10.1016/j.bbrc.2018.04.191
|View full text |Cite|
|
Sign up to set email alerts
|

Spatial localisation of Discoidin Domain Receptor 2 (DDR2) signalling is dependent on its collagen binding and kinase activity

Abstract: Discoidin Domain Receptor 2 (DDR2) is a collagen-binding receptor tyrosine kinase that initiates delayed and sustained tyrosine phosphorylation signalling. To understand the molecular basis of this unique phosphorylation profile, here we utilise fluorescence microscopy to map the spatiotemporal localisation of DDR2 and tyrosine phosphorylated proteins upon stimulation with collagen. We show that cellular phosphorylated proteins are localised to the interface where DDR2 is in contact with collagen and not in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
1
0
0
1
Order By: Relevance
“…Recent studies have reported the co-localization of total and pDDRs in cells with collagen [20,21,36]. Our results expand these observations by showing that higher-order assembly of DDRs into receptor clusters and/or filamentous structures may associate with different morphological states of collagen.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have reported the co-localization of total and pDDRs in cells with collagen [20,21,36]. Our results expand these observations by showing that higher-order assembly of DDRs into receptor clusters and/or filamentous structures may associate with different morphological states of collagen.…”
Section: Discussionsupporting
confidence: 88%
“…Это может зависеть от разных факторов, как внешних, так и внутренних [3,4]. К таким факторам относятся и генетические особенности, в том числе обмена коллагена [5,6]. Знания особенностей обмена коллагена в коже могут помочь в выборе наиболее эффективных процедур во врачебной косметологии и сделать шаг в сторону персонализированной и предиктивной медицины в рассматриваемой области медицинской науки [7].…”
unclassified